Effect of posttranslational modifications and subclass on IgG activity: from immunity to immunotherapy - Nimmerjahn, Falk; Vidarsson, Gestur; Cragg, Mark S. (Nature Immunology, 2023)
Humoral immune responses are characterized by complex mixtures of polyclonal antibody species varying in their isotype, target epitope specificity and affinity. Posttranslational modifications occurring during antibody production in both the antibody variable and constant domain create further complexity and can modulate antigen specificity and antibody Fc-dependent effector functions, respectively. Finally, modifications of the antibody backbone after secretion may further impact antibody activity. An in-depth understanding of how these posttranslational modifications impact antibody function, especially in the context of individual antibody isotypes and subclasses, is only starting to emerge. Indeed, only a minute proportion of this natural variability in the humoral immune response is currently reflected in therapeutic antibody preparations. In this Review, we summarize recent insights into how IgG subclass and posttranslational modifications impact IgG activity and discuss how these insights may be used to optimize therapeutic antibody development.
CRIS-Team Scopus Importer:2023-07-21